Pengaruh Power Lengan Terhadap Kemampuan Smash Ditinjau Dari Panjang Lengan Pada Pemain Bulutangkis DI Kabupaten Takalar - Warfahmi Arif; Sarifin G; Andi Atssam Mappanyukki (UNIVERSITAS NEGERI MAKASSSAR, 2021)
This experimental research aims to determine the effect of arm power on the smash ability of badminton in terms of arm length consisting of long and short. This research was conducted at the Badminton Juang Lapris Building, Takalar Regency from December to January 2021.The experimental method used